2018
DOI: 10.1371/journal.pone.0191065
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing malignancy results in increased prevalence of distinct populations of CD4+ T cells during sepsis

Abstract: The presence of pre-existing malignancy in murine hosts results in increased immune dysregulation and risk of mortality following a septic insult. Based on the known systemic immunologic changes that occur in cancer hosts, we hypothesized that the presence of pre-existing malignancy would result in phenotypic and functional changes in CD4+ T cell responses following sepsis. In order to conduct a non-biased, unsupervised analysis of phenotypic differences between CD4+ T cell compartments, cohorts of mice were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…However, in animals with preexisting cancer, prevention of lymphocyte apoptosis by overexpression of Bcl-2 or using Bim -/mice lead to increased mortality in a pneumonia sepsis model (36). Moreover, we have previously shown that during sepsis, the dysregulated host response to infection may be exaggerated in animals with cancer compared with PH animals (37,38). Significantly increased activation markers (CD25, CD69) and coinhibitory receptors (PD-1, 2B4) expression were found on both CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in animals with preexisting cancer, prevention of lymphocyte apoptosis by overexpression of Bcl-2 or using Bim -/mice lead to increased mortality in a pneumonia sepsis model (36). Moreover, we have previously shown that during sepsis, the dysregulated host response to infection may be exaggerated in animals with cancer compared with PH animals (37,38). Significantly increased activation markers (CD25, CD69) and coinhibitory receptors (PD-1, 2B4) expression were found on both CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…response to sepsis in animals with cancer was characterized by increased activation and inflammation relative to that observed in healthy animals (37). Therefore, blockade of PD-1 may be insufficient to overcome the immune dysregulation in cancer septic animals and potentially may even further amplify the overwhelming inflammation during cancer sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, it has been reported that the ICU and in‐hospital mortality rates for cancer patients with sepsis were 42% and 56%, respectively, frequencies that are much higher than immunocompetent patients . While the etiology behind the increased mortality observed in septic cancer patients compared to previously healthy patients is multifactorial (and likely includes exposure to various anticancer drugs), we previously demonstrated that the presence of cancer (in the absence of any other treatment) negatively impacts the mortality following sepsis, and is associated with phenotypic and functional changes in CD4 + T cell responses following sepsis . Specifically, cancer mice contained more resting memory and activated CD4 + effector cells, exhibited increased frequencies of PD‐1 hi cells that failed to make any cytokines, and a distinct 2B4 hi BTLA hi LAG‐3 hi population that secreted more TNF compared to previously healthy (PH) septic controls.…”
Section: Introductionmentioning
confidence: 97%
“…6 While the etiology behind the increased mortality observed in septic cancer patients compared to previously healthy patients is multifactorial 7 (and likely includes exposure to various anticancer drugs), we previously demonstrated that the presence of cancer (in the absence of any other treatment) negatively impacts the mortality following sepsis, 8 and is associated with phenotypic and functional changes in CD4 + T cell responses following sepsis. 9 Specifically, cancer mice contained more resting memory and activated CD4 + effector cells, exhibited increased frequencies of PD-1 hi cells that failed to make any cytokines, and a distinct 2B4 hi BTLA hi LAG-3 hi population that secreted more TNF compared to previously healthy (PH) septic controls. This observed heterogeneity in co-inhibitory receptor expression and cytokine secretion The chemokine receptor CXCR4 and its ligand CXCL12 are involved in regulating the homeostatic recirculation and retention of myeloid and lymphoid cells in the bone marrow (BM).…”
Section: Introductionmentioning
confidence: 97%
“…Flow cytometric data of tumor samples were manually gated on CD8 + cells using FlowJo software and exported to specifically analyze the CD8 TIL population. These individual files were uploaded to Cytobank (www.cytobank.org), a cloud-based computational platform, and input into SPADE algorithm, as described previously (234).…”
Section: Spade Analysismentioning
confidence: 99%